Prey-processing in the Bornean Keeled Pit Viper, Tropidolaemus subannulatus - Veronica, Martin; Indraneil, Das (Malaysian Nature Society, 2022)
The plasticity of feeding behaviour of predators is strongly influenced by foraging mode, depending on whether they are active foragers, sit-and-wait predators or opportunist feeders. In this study, we conducted ex-situ feeding experiments on the Bornean Keeled Pit-viper, Tropidolaemus subannulatus, a lowland rainforest species distributed on Borneo, Sulawesi and the Philippines. Observations were based on four wild-collected females maintained under laboratory conditions. A total of eight common predatory behaviours were observed that can be classified into three discrete phases, namely, precapture, feeding, and post-feeding phases, during experiments with new-born and live young Rattus norvegicus. In the pre-capture phase, which is temporally the shortest, there were head shifts, eye fixation and head movement towards prey. During the long feeding phase, actions involved strikes, awaiting to ensure prey death, and swallowing of prey. Post-feeding phase is a process of muscular recovery, followed by high-rate of tongue flicks, that can last for up to 15 min. Understanding foraging and prey-handling behaviour has the potential to provide deeper understanding on evolutionary fitness, as well as the biotic and abiotic factors which interacts with the concerned species.